FDG ?PET Fails to Detect a Disease-Specific Phenotype in Rats Transgenic for Huntington's Disease - A 15 Months Follow-up Study - Reilmann, Ralf; Lippross, Veronika; Hölzner, Eva; Gigengack, Fabian; Bohlen, Stefan; Kugel, Harald; Deppe, Michael; Osada, Nani; Lücke, M; Riess, Olaf; Nguyen, Huu Phuc; von Hörsten, Stephan; et al. (Journal of Huntington's Disease, 2015)
FDG-PET detects hypometabolism in premanifest and symptomatic Huntington's disease (HD). A cross-sectional study suggested that whole-brain FDG-PET is capable to detect a phenotype in transgenic (tg) HD rats. Recently, a longitudinal follow-up study showed no FDG-PET changes in tgHD rats. Both studies applied small sample sizes and analysis was limited to whole-brain or striatum.We therefore performed a follow-up study in a larger cohort of tgHD and wild-type (wt) rats encompassing several pre-defined regions of interest (ROIs) and hypothesis free voxel-by-voxel SPM analysis to clarify whether FDG-PET can detect a phenotype in tgHD rats and to determine onset ...and effect sizes of changes over time.N = 19 tgHD- and n = 20 wt-rats, mixed gender, were included. Repeated small animal FDG-?PET and MRI were performed at 5,10,15, and 20 months of age. ROIs encompassing entire brain, cortex, striatum, thalamus, subventricular-zone, and cerebellum were placed manually on the MRI and transferred to the co-registered ?PET. Mean and maximal FDG-PET activities within ROIs were calculated and normalized to cerebellar FDG uptake. Activity and spatially normalized FDG-?PET were compared between groups on a hypothesis-free voxel-by-voxel basis using SPM.FDG uptake showed changes over time in both tgHD- and wt-rats, however, there was no consistent difference between tgHD- and wt-rats in both the manual ROI and SPM analysis.In this transgenic rat model of HD FDG-?PET imaging does not detect significant alterations at the ages investigated. Further investigations are warranted employing other age groups and alternative imaging biomarkers for neuronal degeneration, respectively.
EVALuna2:24981